2015
DOI: 10.5014/ajot.2015.013714
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of a Sensory-Adapted Dental Environment for Children With Autism

Abstract: OBJECTIVE. To provide an example of an occupational therapy feasibility study and evaluate the implementation of a randomized controlled pilot and feasibility trial examining the impact of a sensory-adapted dental environment (SADE) to enhance oral care for children with autism spectrum disorder (ASD). METHOD. Twenty-two children with ASD and 22 typically developing children, ages 6–12 yr, attended a dental clinic in an urban hospital. Participants completed two dental cleanings, 3–4 mo apart, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 19 publications
1
23
0
5
Order By: Relevance
“…The present authors found the framework of Bowen et al (2009) for assessing feasibility also to be applicable regarding intellectual disability-care; it confirmed findings of previous studies on health interventions in patients with advanced, incurable diseases and their caregivers, in older hospitalized patients, and in children with autism (Bowen, Briant, Harris, Hannon, & Buchwald, 2015;Cermak et al, 2015;Pedersen et al, 2015;Siemens et al, 2015). Moreover, the present authors were able to apply all five aspects of Bowen's framework, whereas the previous studies usually addressed only some of them.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The present authors found the framework of Bowen et al (2009) for assessing feasibility also to be applicable regarding intellectual disability-care; it confirmed findings of previous studies on health interventions in patients with advanced, incurable diseases and their caregivers, in older hospitalized patients, and in children with autism (Bowen, Briant, Harris, Hannon, & Buchwald, 2015;Cermak et al, 2015;Pedersen et al, 2015;Siemens et al, 2015). Moreover, the present authors were able to apply all five aspects of Bowen's framework, whereas the previous studies usually addressed only some of them.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies of DCM in nursing home settings reported difficulties similar to ours in fulfilling the DCM-preconditions. These studies concluded that to reach optimal effect of DCM, the implementation requires strong and accurate attention (Brownie & Nancarrow, 2013;Chenoweth et al, 2015;Dichter et al, 2015;Jaycock et al, 2006;Jeon et al, 2012;Quasdorf et al, 2017;Rokstad, Vatne, Engedal, & Selbaek, 2015;Van de Ven, 2014). Increasing the number of realized preconditions is likely to increase the success of the implementation (Chenoweth et al, 2015;Rokstad et al, 2015;Van de Ven et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the view of increasing access to oral care of autistic individuals, it is worth to utilize the least traumatic environment to accommodate the unique sensory and behavioral aberrations of this population. Multiple and simultaneous strategies, including visual, auditory, tactile and video goggles, are advocated to overcome difficulties in communication, social interactions, anxiety and sensory adaptation with dental office environment during providing dental care for ASD patients [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…There is preliminary evidence that guides best practice when implementing environmental modifications such as the use of alternative seating (Bagatell, Mirigliani, Patterson, Reyes, & Test, 2010 Umeda & Deitz, 2011), modifications to the dental environment (Cermak et al, 2015), and changes to sounds and lighting in the classroom (Kinnealey et al, 2012;Reynolds, Kuhaneck, & Pfeiffer, 2016). Other approaches, such as the use of weighted vests, have limited to no evidence to support their continued use (Case-Smith et al, 2015;Watling & Hauer, 2015).…”
Section: Environmental Supports and Adaptationsmentioning
confidence: 99%